The Effect Of Learning Method And Critical Thinking Ability To The Learning Outcomes On Natural Sciences Of Class 5th Student - Chairan Zibar L. Parisu; Arna Juwairiyah; La Sisi (Jurnal Sultra Elementary School, 2020)
This study aimed to determine the effect of teaching methods Teams Games Tournament (TGT) and learning methods Talking Stick and critical thinking skills to the learning outcomes of natural sciences. This research was conducted at the Primary School. The study design using analysis of variance 2 lanes (ANOVA). The results of this study were (1) the results of elementary school students learn science learning with the learning method TGT higher than the results of elementary school students learn science learning with the learning method Talking Stick. (2) There is an interaction effect between teaching methods and students' critical thinking skills to the results of elementary school students learn science. (3) The results of elementary school students learn science which have high critical thinking skills are learned by the learning method TGT has a higher influence than students learning with the learning method Talking Stick. (4) The results of elementary school students learn science that has the ability to think critically low learning TGT learning methods that have lesser influence than the students learning with the learning method Talking StickKeywords: Teams Games Tournament, Talking Stick, Critical Thinking.